PENGGUNAAN CHATGPT SEBAGAI MEDIA PENDUKUNG PEMBELAJARAN AKIDAH AKHLAK DI MADRASAH ALIYAH - Naila Afiyanti; Nur Ramadhani; Salma Adzira; Syarifatul Husni; Nurul Mahfuza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of ChatGPT as a supporting learning medium in Akidah Akhlak learning at Madrasah Aliyah. The research was motivated by the rapid development of artificial intelligence technology in education and the need for innovative learning media that can improve students’ engagement and understanding in Islamic Religious Education. This study explores how ChatGPT supports the learning process, students’ responses toward its use, and its implications for Akidah Akhlak learning. This study employed a qualitative approach using a case study method. The research subjects consisted of teachers and students at Madrasah Aliyah involved in Akidah Akhlak learning activities utilizing ChatGPT. Data were collected through observations, interviews, and documentation. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The findings revealed that the use of ChatGPT as a supporting learning medium positively contributed to students’ learning engagement and understanding of Akidah Akhlak materials. Students showed greater interest and participation during learning activities. ChatGPT facilitated easier access to explanations, examples, and learning references interactively and quickly. However, the study also found several challenges, such as students’ dependence on instant answers, limited critical verification of information, and the need for teacher supervision in utilizing AI-based learning tools.